The effect of non-contributory pensions on the subjective wellbeing of older adults in Mexico - Juárez, Laura; Rodríguez Piña, Yunuen Nicte (Estudios Económicos de El Colegio de México, 2021)
In this article, we estimate the impact of a non-contributory pension, in operation at the federal level between 2007 and 2012, on the subjective wellbeing of older adults. Our results suggest that, on average, this pension had a positive, and statistically significant, effect on the subjective wellbeing of older women, but not on that of older men. However, a heterogeneous impact analysis, based on socioeconomic vulnerability, reveals that there are positive impacts of this pension for men who speak an indigenous language and that the positive impacts are more pronounced for older women who did not complete their primary education.